The intracerebral injection of Aβ1-42 oligomers does not invariably alter seizure susceptibility in mice - Vande Vyver, Maxime; Daeninck, Louise; De Smet, Gino; Aourz, Najat; Sahu, Surajit; Engelborghs, Sebastiaan; Pauwels, Kris; De Bundel, Dimitri; Smolders, Ilse (Frontiers in Aging Neuroscience, 2023)
Objectives Epileptiform activity and seizures are present in patients with Alzheimer’s disease (AD) and genetic animal models of AD. Amyloid beta 1-42 (Aβ1-42) oligomers are thought to be crucial in AD and can cause neuronal hyperexcitability in vitro. However, it is unclear whether these Aβ1-42 oligomers cause the increased seizure susceptibility in vivo in people with AD and in AD animal models, nor via which mechanisms it would do so. We investigated this question by injecting Aβ1-42 oligomers intracerebrally in mice and assessed its impact on seizure susceptibility. Materials and methods We performed a single intracerebral injection of synthetic Aβ1-42 oligomers or scrambled Aβ1-42 in NMRI mice in three different cohorts and subjected them to an i.v. infusion of a chemoconvulsant. We evoked the seizures 1.5 h, 1 week, or 3 weeks after the intracerebral injection of Aβ1-42 oligomers, covering also the timepoints and injection locations that were used by others in similar experimental set-ups. Results With a thioflavine T assay and transmission electron microscopy we confirmed that Aβ1-42 monomers spontaneously aggregated to oligomers. We did not find an effect of Aβ1-42 oligomers on susceptibility to seizures – evoked 1.5 h, 1 week or 3 weeks – after their intracerebral injection. Significance The lack of effect of Aβ1-42 oligomers on seizure susceptibility in our experiments contrasts with recent findings in similar experimental set-ups. Contradicting conclusions are frequent in experiments with Aβ1-42 and they are often attributed to subtle differences in the various aggregation forms of the Aβ1-42 used in different experiments. We confirmed the presence of Aβ1-42 oligomers with state-of-the-art methods but cannot ascertain that the protein aggregates we used are identical to those used by others. Whether our findings or those previously published best represent the role of Aβ1-42 oligomers on seizures in AD remains unclear.